2009
DOI: 10.2353/ajpath.2009.090295
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of CXCL12 Expression and FoxP3+ Cell Infiltration with Human Papillomavirus Infection and Clinicopathological Progression of Cervical Cancer

Abstract: Human cervical cancer is an immunogenic tumor with a defined pattern of histopathological and clinical progression. Tumor-infiltrating T cells contribute to immune control of this tumor; however, cervical cancer dysregulates this immune response both through its association with human papillomavirus (HPV) infection and by producing cytokines and chemokines. Animal tumor models have revealed associations between overproduction of the chemokine stromal cell-derived factor-1 (SDF-1 or CXCL12) and dysregulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 30 publications
0
49
0
1
Order By: Relevance
“…Therefore, the population of FOXP3 + T cells was significantly higher in patients with cervical cancer than in healthy subjects. Jaafar et al [33] found that in animal models, cytokine overexpression in cervical cancer contributed to the accumulation of FOXP3 + T cells. Further studies reported that FOXP3 expression was changed in benign and malignant cervical lesions.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the population of FOXP3 + T cells was significantly higher in patients with cervical cancer than in healthy subjects. Jaafar et al [33] found that in animal models, cytokine overexpression in cervical cancer contributed to the accumulation of FOXP3 + T cells. Further studies reported that FOXP3 expression was changed in benign and malignant cervical lesions.…”
Section: Discussionmentioning
confidence: 98%
“…22 Correlation between Treg infiltration and CXCL12 expression has been found in cervical cancer. 23 Classical Tregs inhibit T cells in lymphoid organs. Although CXCL12 is expressed in bone marrow, G-CSF has been reported to reduce CXCL12 in bone marrow.…”
Section: Acquisition Of Metastatic Potential In Primary Tumorsmentioning
confidence: 99%
“…4 The expression of this chemokine SDF-1 was reported to be significantly increased in cervical epithelium as the neoplastic lesions progressed from preinvasive to invasive cancer. 5 In the other way, the expression of chemokine receptor 4 (CXCR4), which acts as receptor to SDF-1, could be detected in most primary tumors, and its strong expression in the primary tumor was associated with metastatic spread to pelvic nodes, whereas normal cervical epithelium was detected negative for the expression of SDF-1 and its receptor CXCR4. In addition, SDF-1 expression was reported to be directly correlated with known determinants of immune dysregulation, such as HPV infection itself and regulatory T-cell infiltration.…”
mentioning
confidence: 99%